Applying potassium fertilizer improves sheath rot disease tolerance and decreases grain yield loss in rice (Oryza sativa L.). (January 2021) - Zhang, Jianglin; Hou, Wenfeng; Ren, Tao; Cong, Rihuan; Zhao, Zhuqing; Lu, Jianwei; Li, Xiaokun
Abstract: Sheath rot disease (ShR) is a new threat in rice production, causing yield losses of 10–85%. Potassium (K) plays an important role in improving rice tolerance to disease and ensuring yield stability. Two-year field studies with four K application rates were conducted to investigate the impacts of K application on ShR disease incidence and yield loss caused by ShR. The results showed that K application significantly decreased the ShR disease incidence by 20.0–72.1% and 37.8–89.9% in the 2017 and 2018 rice growing seasons, respectively. Similarly, K application profoundly alleviated the severity of ShR. Therefore, the total yield loss rate (TYLR) considerably decreased with increasing K application rates. Compared with the zero-K application, K application decreased the TYLR by averages of 59.3% and 74.4% in 2017 and 2018, respectively. The filled-grain rate decrease contributed the most to the TYLR in ShR disease. In addition, K starvation increased the C/N ratio of the flag leaf sheath (FLS), which was negatively correlated with the ShR disease index (DI). In contrast, soluble sugar (SS) accumulation in the FLS was positively correlated with the DI. K application significantly increased the apparent transferred mass of non-structural carbohydrates (NSCs) from stems to grains (ATMNSC ). Moreover, the stem ATMNSC of diseased plants contributed more to the final grain yield than did that of healthy plants. During ShR disease, K application significantly alleviated the decrease in the filled-grain rate and harvest index by enhancing the stem ATMNSC, according to an exponential equation relationship between the stem ATMNSC and the filled-grain rate of diseased rice. Maintaining the stem K concentration in the range of 1.53–1.74% at the heading stage could increase the stem ATMNSC to mitigate the TYLR. These results emphasize the importance of K in rice to improve the potential for alleviating ShR disease. Graphical abstract: Image 1 Highlights: K application considerably decreased the severity of ShR disease . K application decreased the TYLR caused by ShR by increasing the filled-grain rate. K application alleviated ShR predominately by increasing the ATMNSC from stems to grains. Maintaining the stem K concentration in the range of 1.53–1.74% could mitigate ShR disease.